Costs and benefits of natural transformation in Acinetobacter baylyi. Issue 1 (December 2017) - Hülter, Nils; Sørum, Vidar; Borch-Pedersen, Kristina; Liljegren, Mikkel; Utnes, Ane; Primicerio, Raul; Harms, Klaus; Johnsen, Pål
Abstract Background Natural transformation enables acquisition of adaptive traits and drives genome evolution in prokaryotes. Yet, the selective forces responsible for the evolution and maintenance of natural transformation remain elusive since taken-up DNA has also been hypothesized to provide benefits such as nutrients or templates for DNA repair to individual cells. Results We investigated the immediate effects of DNA uptake and recombination on the naturally competent bacteriumAcinetobacter baylyi in both benign and genotoxic conditions. In head-to-head competition experiments between DNA uptake-proficient and -deficient strains, we observed a fitness benefit of DNA uptake independent of UV stress. This benefit was found with both homologous and heterologous DNA and was independent of recombination. Recombination with taken-up DNA reduced survival of transformed cells with increasing levels of UV-stress through interference with nucleotide excision repair, suggesting that DNA strand breaks occur during recombination attempts with taken-up DNA. Consistent with this, we show that absence of RecBCD and RecFOR recombinational DNA repair pathways strongly decrease natural transformation. Conclusions Our data show a physiological benefit of DNA uptake unrelated to recombination. In contrast, recombination during transformation is a strand break inducing process that represents a previously unrecognized cost of natural transformation.